6-Gingerol Slightly Reduces Hepatic Endoplasmic Reticulum Stress Markers in Rats with High-Fat, High-Fructose Diet-Induced Metabolic Syndrome - Ahmad, Nouman; Syarifah Dewi; Soetikno, Vivian (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2025)
Metabolic syndrome (MetS) is linked to hepatic endoplasmic reticulum (ER) stress. This study evaluated 6-gingerol’s potential to alleviate ER stress in a high-fat high-fructose (HFHF)-induced MetS rat model. Male Sprague-Dawley rats (8 weeks, 180–220 g) were assigned to five groups: Normal, HFHF, and HFHF with 6-gingerol (50, 100, or 200 mg/kg). The Normal group received a standard diet, while others had HFHF for 16 weeks. From Week 8, intervention groups received 6-gingerol daily. Except for Normal, other groups also received Streptozotocin (22mg/kg, i.p.) at Week 8. At Week 16, rats were euthanized, and liver tissues collected to assess ER stress markers (GRP78, IRE1, TRAF2, PERK, CHOP) via qPCR and apoptotic markers (Bax, Bcl-2) via ELISA. 6-Gingerol slightly reduced liver ER stress markers, including GRP78 (P=0.392), CHOP (P=0.798), IRE1 (P=0.419), TRAF2 (P=0.470), and PERK (P=0.357), but these changes were not significant. Similarly, apoptotic markers Bax and Bcl-2 showed no significant differences, though the Bax/Bcl-2 ratio decreased (P=0.186). These results indicate that 6-gingerol had only a slight effect on ER stress and apoptosis within the parameters of this experiment.